Development of a multiplex real-time PCR assay using two thermocycling platforms for detection of major bacterial pathogens associated with bovine respiratory disease complex from clinical samples. (November 2018) - Loy, John D.; Leger, Laura; Workman, Aspen M.; Clawson, Michael L.; Bulut, Ece; Wang, Bing
Bovine respiratory disease complex (BRDC) is one of the most significant diseases of cattle. Bacterial pathogens involved in BRDC include Mannheimia haemolytica, Mycoplasma bovis, Histophilus somni, and Pasteurella multocida . We developed and evaluated a multiplexed real-time hydrolysis probe (rtPCR) assay using block-based Peltier and rotary-based thermocycling on lung tissue, nasal swabs, and deep nasopharyngeal swabs. The rtPCR results were compared to culture or a gel-based M. bovis PCR using statistical analysis to determine optimum quantification cycle (Cq) cutoffs to maximize agreement. The limits of detection were 1.2–12 CFU/reaction for each pathogen. M. haemolytica was the most prevalent organism detected by rtPCR, and was most frequently found with P. multocida . The rtPCR assay enabled enhanced levels of detection over culture for all pathogens on both thermocycling platforms. The rotary-based thermocycler had significantly lower Cq cutoffs (35.2 vs. 39.7), which maximized agreement with gold standard culture or gel-based PCR results following receiver operating characteristic analysis to maximize sensitivity (Se) and specificity (Sp). However, overall assay Se and Sp were similar on both platforms (80.5% Se, 88.8% Sp vs. 80.1% Se, 88.3% Sp). Implementation of these tests could enhance the detection of these pathogens, and with high-throughput workflows could reduce assay time and provide more rapid results. The assays may be especially valuable in identifying coinfections, given that many more antemortem samples tested in our study were positive for 2 or more pathogens by rtPCR ( n = 125) than were detected using culture alone ( n = 25).